LA ÉTICA Y SU INFLUENCIA EN LA GESTIÓN INSTITUCIONAL DE ENTIDADES EDUCATIVAS PRIVADAS DE ENSEÑANZA SUPERIOR - Begazo Villanueva, José Domingo (2011)
Educational institutions have significant social and cultural functions in the construction of society and with respect to the significant changes taking place in the world, especially when looking for different ways to reduce the inequitable distribution of wealth, promote social mobility and study and formulate possible solutions to priority problems. The values and ethical behavior are some of these issues. Professions and professionals from all areas of knowledge, occupy a significant place in the social world, as they provide goods and services required by society itself. Their performance and actions are always on the look of the sectors, groups and individuals (local, regional, national and international). Ethical behavior is an intrinsic part of the profession and the meaning and life plans of the subjects. It is also with the professional and technical competence, so people can better appreciate their work. Professional ethics is an interdisciplinary field, which can help reduce the isolation that are the specialties, to integrate a holistic approach. The ethical responsibility of all professions, not just each of them, but also the fields of interaction that occur to solve complex social problems.